Population diversity and the portfolio effect in an exploited species - Schindler, Daniel E.; Hilborn, Ray; Chasco, Brandon; Boatright, Christopher P.; Quinn, Thomas P.; Rogers, Lauren A.; Webster, Michael S. (Nature (London), 2010)
Population diversity boosts fishery resilience The role of species diversity in ecosystem stability is well appreciated, but population diversity within a species is also important and often overlooked. An analysis of over 50 years of data on sockeye salmon returns to the rivers of Bristol Bay, Alaska, shows just how important this portfolio effect — so-called by analogy with risk-spreading in financial markets — can be. The sockeye salmon fishery is one of the most valuable in the United States, with more than 60% of it coming from this region. The fact that it is made up of several hundred discrete populations makes the observed population variability about half what would be expected in a single homogenous population, and numerical modelling predicts that a homogenous population would be subject to ten times more fisheries closures. In terms of fisheries management, this work suggests that reducing the homogenizing effects of hatcheries on genetic diversity, protecting weak stocks from over-harvesting in mixed stock fisheries, and maintaining intact habitat networks should be prioritized. The value of having a diversity of species within an ecosystem is well appreciated: species-rich communities are thought to produce more stable ecosystem services. But population diversity within a species is important too. Here, the effects of diversity in population and life history in a heavily exploited Alaskan salmon species are quantified. The results show that population diversity increases the resilience of this ecosystem, and hence the value of salmon fisheries. One of the most pervasive themes in ecology is that biological diversity stabilizes ecosystem processes and the services they provide to society 1 , 2 , 3 , 4 , a concept that has become a common argument for biodiversity conservation 5 . Species-rich communities are thought to produce more temporally stable ecosystem services because of the complementary or independent dynamics among species that perform similar ecosystem functions 6 . Such variance dampening within communities is referred to as a portfolio effect 7 and is analogous to the effects of asset diversity on the stability of financial portfolios 8 . In ecology, these arguments have focused on the effects of species diversity on ecosystem stability but have not considered the importance of biologically relevant diversity within individual species 9 . Current rates of population extirpation are probably at least three orders of magnitude higher than species extinction rates 10 , so there is a pressing need to clarify how population and life history diversity affect the performance of individual species in providing important ecosystem services. Here we use five decades of data from Oncorhynchus nerka (sockeye salmon) in Bristol Bay, Alaska, to provide the first quantification of portfolio effects that derive from population and life history diversity in an important and heavily exploited species. Variability in annual Bristol Bay salmon returns is 2.2 times lower than it would be if the system consisted of a single homogenous population rather than the several hundred discrete populations it currently consists of. Furthermore, if it were a single homogeneous population, such increased variability would lead to ten times more frequent fisheries closures. Portfolio effects are also evident in watershed food webs, where they stabilize and extend predator access to salmon resources. Our results demonstrate the critical importance of maintaining population diversity for stabilizing ecosystem services and securing the economies and livelihoods that depend on them. The reliability of ecosystem services will erode faster than indicated by species loss alone.